Hierarchical Composite Self‐Sorted Supramolecular Gel Noodles. Issue 17 (15th March 2023) - Marshall, Libby J.; Wallace, Matthew; Mahmoudi, Najet; Ciccone, Giuseppe; Wilson, Claire; Vassalli, Massimo; Adams, Dave J.
Abstract: Multicomponent supramolecular systems can be used to achieve different properties and new behaviors compared to their corresponding single component systems. Here, a two‐component system is used, showing that a non‐gelling component modifies the assembly of the gelling component, allowing access to co‐assembled structures that cannot be formed from the gelling component alone. The systems are characterized across multiple length scales, from the molecular level by NMR and CD spectroscopy to the microstructure level by SANS and finally to the material level using nanoindentation and rheology. By exploiting the enhanced mechanical properties achieved through addition of the second component, multicomponent noodles are formed with superior mechanical properties to those formed by the single‐component system. Furthermore, the non‐gelling component can be triggered to crystallize within the multicomponent noodles, allowing the preparation of new types of hierarchical composite noodles. Abstract : Multicomponent assembly of 2NapFF with the structurally similar functionalized dipeptide 2NapLG causes changes to the formed first‐order supramolecular structures. These changes to assembly allow access to new properties and behaviors. This multicomponent system can be used to form mechanically robust supramolecular noodles. Through a change in external conditions (a reduction in pH), crystals can be formed within these noodles.